2018
DOI: 10.1080/13697137.2017.1421924
|View full text |Cite|
|
Sign up to set email alerts
|

Role of topical oxytocin in improving vaginal atrophy in postmenopausal women: a randomized, controlled trial

Abstract: Oxytocin gel is useful in the restoration of the vaginal epithelium in cases of postmenopausal atrophic vaginitis. Further studies with a longer follow-up period are required to test the long-term effects of oxytocin as a treatment for vaginal atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 12 publications
4
36
0
Order By: Relevance
“…Roshangar et al in their study found that injection of 1 IU/gr oxytocin could significantly increase the endometrial thickness in the rat after 48 hours [24] In the present study, all of the subjective symptoms of vaginal atrophy significantly improved in the and used 600 IU oxytocin gel or placebo to relief the vaginal atrophy and followed patients for one month. Their results showed that all subjective and objective symptoms of vaginal atrophy decreased significantly in the oxytocin group [18]. These results are similar to what we found in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Roshangar et al in their study found that injection of 1 IU/gr oxytocin could significantly increase the endometrial thickness in the rat after 48 hours [24] In the present study, all of the subjective symptoms of vaginal atrophy significantly improved in the and used 600 IU oxytocin gel or placebo to relief the vaginal atrophy and followed patients for one month. Their results showed that all subjective and objective symptoms of vaginal atrophy decreased significantly in the oxytocin group [18]. These results are similar to what we found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The role of oxytocin on vaginal atrophy was examined first by Al-Saqi et al, and they found that oxytocin is a useful means for reducing vaginal atrophy in postmenopausal women [17]. Recently another study examined the effect of oxytocin vaginal gel on vaginal atrophy and the results showed that oxytocin could significantly reduce the vaginal atrophy after 30 days of the intervention [18]. There are only a few studies that evaluated the impact of vaginal gel of oxytocin on vaginal atrophy that one of them followed participants for four weeks and the other for seven weeks.…”
Section: Introductionmentioning
confidence: 99%
“…A study assessed the effect of prostaglandin IU oxytocin gel or placebo to relief the vaginal atrophy and followed patients for one month. Their results showed that all subjective and objective symptoms of vaginal atrophy decreased significantly in the oxytocin group [18]. These results are similar to what we found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…One of the limitations of this study is; we did not assess the level of blood estrogen of participants. However, other studies showed that oxytocin did not affect the blood estrogen level [18]. In this study because of financial constraints, we were not able to prepare disposable applicator and used one applicator to transfer oxytocin gel or placebo into vagina.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 95%
See 1 more Smart Citation